Comparative Genomics of the Major Histocompatibility Complex (MHC) of Felids - Plasil, Martin; Futas, Jan; Jelinek, April; Burger, Pamela A.; Horin, Petr (Frontiers in Genetics, 2022)
This review summarizes the current knowledge on the major histocompatibility complex (MHC) of the family Felidae. This family comprises an important domestic species, the cat, and a variety of free-living felids, including several endangered species. As such, the Felidae have the potential to be an informative model for studying different aspects of the biological functions of MHC genes, such as their role in disease mechanisms and adaptation to different environments, as well as the importance of genetic diversity for conservation issues in free-ranging or captive populations. Despite this potential, the current knowledge on the MHC in the family as a whole is fragmentary and based mostly on studies of the domestic cat and selected species of big cats. The overall structure of the domestic cat MHC is similar to other mammalian MHCs following the general scheme “centromere-MHC class I-MHC class III-MHC class II” with some differences in the gene contents. An orthologue of the non-classical class I HLA-E gene has not been identified and the class II DQ and DP genes are missing or pseudogenized, respectively. A comparison with available genomes of other felids showed a generally high level of conservation of the MHC region. Fragmentary information on the role of felid MHC genes in diseases is available. No information is available on interaction of MHC class I molecules with Natural Killer (NK) cell receptors. A comparison of complex genomic regions encoding NK cell receptors (the Leukocyte Receptor Complex, LRC and the Natural Killer Cell Complex, NKC) in the available felid genomes showed a higher variability in the NKC compared to the LRC and the MHC regions. Studies of the genetic diversity of domestic cat populations have focused mainly on DRB genes. Higher levels of MHC diversity were observed in stray cats compared to pure breeds. Immunogenetic analysis in wild felids has only been performed on MHC loci in tigers, Namibian leopards and cheetahs. This information is important as part of current conservation tasks to assess the adaptive potential of endangered wild species at the human-wildlife interface, which will be essential for preserving biodiversity in a functional ecosystem.